Evaluation of MicrocinE492 gene presence in Klebsiella pneumoniae isolated from clinical samples. - Islam, Faria (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.